Parental control and monitoring of young people's sexual behaviour in rural North-Western Tanzania: Implications for sexual and reproductive health interventions - Wamoyi, Joyce (BioMed Central, 2011)
BACKGROUND: Parenting through control and monitoring has been found to have an effect on young people's sexual behaviour. There is a dearth of literature from sub-Saharan Africa on this subject. This paper examines parental control and monitoring and the implications of this on young people's sexual decision making in a rural setting in North-Western Tanzania. METHODS: This study employed an ethnographic research design. Data collection involved 17 focus group discussions and 46 in-depth interviews conducted with young people aged 14-24 years and parents/carers of young people within this age-group. Thematic analysis was conducted with the aid of NVIVO 7 software. RESULTS: Parents were motivated to control and monitor their children's behaviour for reasons such as social respectability and protecting them from undesirable sexual and reproductive health (SRH) outcomes. Parental control and monitoring varied by family structure, gender, schooling status, a young person's contribution to the economic running of the family and previous experience of a SRH outcome such as unplanned pregnancy. Children from single parent families reported that they received less control compared to those from both parent families. While a father's presence in the family seemed important in controlling the activities of young people, a mother's did not have a similar effect. Girls especially those still schooling received more supervision compared to boys. Young women who had already had unplanned pregnancy were not supervised as closely as those who hadn't. Parents employed various techniques to control and monitor their children's sexual activities. CONCLUSIONS: Despite parents making efforts to control and monitor their young people's sexual behaviour, they are faced with several challenges (e.g. little time spent with their children) which make it difficult for them to effectively monitor them. There is a need for interventions such as parenting skills building that might enable parents to improve their relationships with children. This would equip parents with the appropriate skills for positive guidance and monitoring of their children and avoid inappropriate parenting behaviour. As much as parents focus their attention on their school going daughters, there is a need to also remember the out-of-school young people as they are also vulnerable to adverse SRH outcomes.